Review of Potential Ecological Impacts of Peaceful Robotic Drone Use and Policy Implications for Developing Countries (2015)
A review has been carried out on the potential ecological impacts of peaceful or civilian robotic drone use and its policy implications for developing countries. The author delves into the emergence of what has become today known as drones right from the late 16th century it was first used as a hot - air balloon through its evolvement over the decades inspired by the need for national defence and global peace. The article highlights the rapid departure from the tragic use of military - grade drones to peaceful or civilian uses in the last decade to policy implications for developing countries. The article gives succinct analyses of the reported and potential pros and cons associated with peaceful drone use in developed and developing countries with the aim of assisting the later in this unavoidable policy decision at hand. Suggestions are made on the way forward through approaches to arrive at policy criteria on peaceful robotic drone use in accordance with cultural, developmental, ethical and ecological needs, aspirations and peculiarities of developing countries in need of such a framework.